Modification of the surface of titanium with multifunctional chimeric peptides to prevent biofilm formation via inhibition of initial colonizers - Zhang X (Dove Medical Press, 2018)
Xi Zhang,1 Hongjuan Geng,1 Lei Gong,2 Qian Zhang,1 Hongjie Li,1 Xu Zhang,1 Yonglan Wang,1 Ping Gao1 1School and Hospital of Stomatology, Tianjin Medical University, Tianjin 300070, China; 2Department of Esophageal Cancer, Tianjin’s Clinical Research Center for Cancer and Key Laboratory of Cancer Prevention and Therapy, National Clinical Research Center for Cancer, Tianjin Medical University Cancer Institute and Hospital, Tianjin 300070, China Background: Prevention of bacterial colonization remains a major challenge in the field of oral implant devices. Chimeric peptides with binding, antimicrobial, and osteogenesis motifs may provide a promising alternative for the inhibition of biofilm formation on titanium (Ti) surfaces. Methods: In this study, chimeric peptides were designed by connecting an antimicrobial sequence from human β-defensin-3 with a Ti-binding sequence and arginine-glycine-aspartic acid using a glycine-glycine-glycine linker. Binding to the Ti substrate and antimicrobial properties against streptococci were evaluated. Significant improvement in reduction of bacterial colonization onto the Ti surface was observed, with or without the presence of saliva or serum. The MC3T3-E1 cells grew well on the modified Ti surfaces compared with the control group. Results: The data showed that the three peptide functional motifs maintained their respective functions, and that the antibiofilm mechanism of the chimeric peptide was via suppression of sspA and sspB gene expression. Conclusion: These results indicated that the endogenous peptide fragments engineered on the Ti surface could provide an environmentally friendly approach for improving the biocompatibility of oral implants. Keywords: multifunctional chimeric peptide, modification of titanium surface, human β-defensin-3, Ti-binding peptide-1, arginine-glycine-aspartic acid-containing peptides